The effects of instability core training on balance ability and paddling performance among young male Chinese flatwater sprint kayakers: a randomized controlled trial - Gao, Jianxin; Gong, Zhigang; Samsudin, Shamsulariffin; Abdullah, Borhannudin; Dev Omar Dev, Roxana (BioMed Central, 2025)
Background: Instability core training (ICT) has been widely used in various sports as a training method to enhance athletes' balance ability and athletic performance. The study aimed to examine the impact of ICT performed on unstable surfaces (BOSU balls, Swiss balls, and Wobble boards) versus traditional core training (TCT) performed on stable surfaces (floor and bench) on balance ability and paddling performance among young male Chinese kayakers. Method: A randomized controlled trial (RCT) recruited 63 eligible kayakers aged 16–19 years from the Nanchang Yao Lake kayaking training base in Jiangxi province, China. Participants were randomly assigned to the ICT group and the TCT group. Both groups completed a 12-week core training program consisting of 1-h sessions, 3 times/week. Static balance ability was assessed using the Flamingo Balance Test (FBT), while dynamic balance ability was measured using the Star Excursion Balance Test (SEBT). Paddling parameters were evaluated using the average stroke power and stroke rate for the men’s K-1 200 m land dynamometer/ergometer sprint tests. Statistical analyses were conducted via multivariate analysis of variance (MANOVA), with the significance level set at P < 0.05. Results: The analysis for within-group effects demonstrated statistically significant improvements in static balance ability, dynamic balance ability, average stroke power, and stroke rate variables between the pre-test and post-test in both the ICT and TCT groups (p < 0.05). No statistically significant differences were observed in the pre-test (p > 0.05) for between-group effects. In contrast, statistically significant differences were found between the ICT and TCT groups in the post-test for all balance ability and paddling parameter variables (p < 0.05). Conclusion: The findings suggest that while TCT significantly improves balance ability and paddling performance, ICT is more effective than TCT over a 12-week intervention among young male Chinese kayakers. Therefore, it can replace TCT, as it promotes better improvement in balance ability and paddling parameters for young male Chinese kayakers. Trial registration. The full name of the registry: Effect of instability resistance training on balance, core muscle strength, and athletic performance. The trial registration number is NCT06432595. The date of registration is 07/01/2024. The trial registration platform is ClinicalTrials.gov PRS (https://clinicaltrials.gov/).